2020
DOI: 10.3389/fphar.2020.498758
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TGF-β and Autophagy Pathways in Pathogenesis of Diabetes: A Comprehensive Review on Biological and Pharmacological Insights

Abstract: Despite recent advancements in clinical drugs, diabetes treatment still needs further progress. As such, ongoing research has attempted to determine the precise molecular mechanisms of the disorder. Specifically, evidence supports that several signaling pathways play pivotal roles in the development of diabetes. However, the exact molecular mechanisms of diabetes still need to be explored. This study examines exciting new hallmarks for the strict involvement of autophagy and TGF-b signaling pathways in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 218 publications
1
14
0
Order By: Relevance
“…The patients with age-related cataract who underwent phacoemulsification were mostly of older age. They possibly have a higher prevalence of metabolic diseases (such as diabetes [ 43 ] and liver diseases [ 44 ]). Moreover, Zhu et al [ 45 ] found that in cataract patients, the concentration of TGF- β 2 decreased while nuclear color darkens.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with age-related cataract who underwent phacoemulsification were mostly of older age. They possibly have a higher prevalence of metabolic diseases (such as diabetes [ 43 ] and liver diseases [ 44 ]). Moreover, Zhu et al [ 45 ] found that in cataract patients, the concentration of TGF- β 2 decreased while nuclear color darkens.…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 activates IKK, which in turn phosphorylate IκBα, leading to proteasomal degradation of IKBα and the release of NF-kB p65-p50 heterodimer resulting in NF-κB activation. ( Hydarpoor et al, 2020 ). Studies have demonstrated that TGF-TAK1 also induces NF-kB activation in murine B cells, hepatocytes and head and neck squamous cell carcinoma (HNSCC) cells ( Loren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we found that CM from hypoxic BMSCs increased SMAD2 phosphorylation levels and SMAD4 localization in the nuclei of epidermal cells, suggesting SMAD pathway activation in epidermal cells. In TGF-β1/SMAD signaling, the binding of TGF-β1 to its receptor complex activates SMAD2/ SMAD3 through direct phosphorylation and further forms a trimer with SMAD4 that subsequently translocates into the nucleus to facilitate gene transcription [44]. Regarding the essential role of the TGF-β1/SMAD signaling pathway in the modulation of cellular behavior, we hypothesized that SMADs are the pivotal downstream mediators of epidermal cell autophagy activation in response to hypoxic BMSC-derived CM.…”
Section: Discussionmentioning
confidence: 99%